The Spending Challenge of Achieving the SDGs in South Asia : Lessons from India - Garcia-Escribano, Mercedes; Mogues, Tewodaj; Moszoro, Mariano; Soto, Mauricio (Washington, D.C. : International Monetary Fund, 2021)
South Asia has experienced significant progress in improving human and physical capital over the past few decades. Within the region, India has become a global economic powerhouse with enormous development potential ahead. To foster human and economic development, India has shown a strong commitment to the Sustainable Development Goals (SDG) Agenda. This paper focuses on the medium-term development challenges that South Asia, and in particular India, faces to ensure substantial progress along the SDGs by 2030. We estimate the additional spending needed in critical areas of human capital (health and education) and physical capital (water and sanitation, electricity, and roads). We document progress on these five sectors for India relative to other South Asian countries and discuss implications for policy and reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Economic Development; Housing; Microeconomic Analyses of Economic Development; National Government Expenditures and Related Policies; Other Public Investment and Capital Stock